Análise prosopográfica dos Deputados Federais eleitos de Passo Fundo/RS (1945-1985) - Fogaça, Akira Tanaka da Silva (2020)
The purpose of this research is to carry out a prosopographic analysis of the deputies federal districts of Passo Fundo/RS from the period 1945 to 1985 in order to verify the profile socioeconomic status of parliamentarians representing Passo Fundo. The source will be the information contained in the database of the Rio Grande Legislative Assembly website do Sul, Chamber of Federal Deputies, Superior Electoral Court, Regional Court Electoral Election of Rio Grande do Sul, from Fundação Getúlio Vargas - Research and Documentation of Contemporary History of Brazil – FGV/CPDOC and also books and articles that deal with the topic. Let’s understand what a prosopographic analysis is about, or method of collective biographies consisting of an investigation of common characteristics of a group of actors in history through a collective study of their lives. In the first chapter analyzes the profile of federal deputies elected by Passo Fundo in the period from 1945 to 1964, a brief history of the creation of Parliament in Brazil to the present day. In the second chapter will analyze the profile of federal deputies elected by the municipality of Passo Fundo/RS between the years 1964 to 1985. Within each electoral year, the results of the elections for governor and federal deputy of Rio Grande do Sul and at the end of In each chapter, the results of the politicians who were elected to the position of the federal legislative branch by the municipality of Passo Fundo. At the end, an analysis of the entire period (1945-1985) of its characteristics that predominated for the population the elect as their representatives.